The Challenges of State Junior High School Teachers in Distance Learning During The Covid-19 Pandemic - Masduki Ahmad (AL-ISHLAH: Jurnal Pendidikan, 2022)
The outbreak of the Covid-19 pandemic has resulted in teachers who are one of the stakeholders’ education having to quickly adapt to changes in the learning system, which were initially face-to-face and then turned into virtual faces. This sudden change also caused a lot of anxiety experienced by the teacher. Therefore, this study aims to determine teachers’ challenges during distance learning. This study uses a qualitative approach with a descriptive method. In this study, the informants were fourth teachers of state junior high school 8 Cilacap. Data was obtained from observations, interviews, and documentation using analytical techniques in reduction, classification, and conclusions. The results showed five challenges for teachers during distance learning: planning lessons, preparing students, motivating students, instilling character in students, and unstable internet networks. The teacher finally looks for the best way or solution to overcome it, namely by discussing with students using various learning technologies or applications, collaborating with parents, and participating in training to improve their competencies.